Evaluating Platelet-Large Cell Ratio (P-LCR) as an Accessible Biomarker for Myocardial Injury in Acute Coronary Syndrome - Muhammad Riza Lubis; Dewi Indah Sari Siregar; Malayana Rahmita Nasution; Hana Fauziyah (HM Publisher, 2025)
Background: The accurate and timely diagnosis of acute coronary syndrome (ACS) in resource-limited healthcare settings is critically hampered by the high cost and limited availability of the gold-standard biomarker, Troponin I. This study aimed to conduct a preliminary evaluation of the association between two accessible platelet indices derived from the complete blood count—the platelet-large cell ratio (P-LCR) and the immature platelet fraction (IPF)—and the quantitative degree of myocardial injury in patients with ACS. Methods: An exploratory, cross-sectional study was conducted on 51 consecutive patients diagnosed with ACS at a tertiary referral hospital in Medan, Indonesia. The relationship between admission P-LCR, IPF, and Troponin I was assessed using a multi-faceted statistical approach, including Spearman's rank correlation, an exploratory multivariable linear regression model, and a Receiver Operating Characteristic (ROC) curve analysis. A post-hoc power analysis was performed to contextualize the findings. Results: The study was found to be statistically underpowered (power ≈ 60%) to reliably detect weak correlations. A statistically significant but weak positive correlation was observed between P-LCR and Troponin I levels (Spearman's ρ = 0.31, p = 0.026). This association remained significant after adjusting for age, gender, and ACS subtype, but the overall model demonstrated minimal explanatory power (Adjusted R² = 0.18). The ROC analysis for P-LCR in discriminating between normal and elevated Troponin I was poor (Area Under the Curve = 0.65; 95% CI: 0.50 - 0.79). No significant correlation was found between IPF and Troponin I (p = 0.093). Conclusion: P-LCR exhibits a weak, independent statistical association with the degree of myocardial injury in ACS patients. However, its poor discriminatory performance, coupled with the profound methodological limitations of this preliminary study, demonstrates that P-LCR is not a clinically useful biomarker for the identification or stratification of myocardial injury. These findings underscore the significant translational gap between a plausible biological hypothesis and a clinically viable diagnostic tool, highlighting the immense complexities that must be addressed in future, more robustly designed research.